The effects of plant extracts on microbial community structure in a rumen-simulating continuous-culture system as revealed by molecular profiling - Ferme, D; Banjac, M; Calsamiglia, S; Busquet, M; Kamel, C; Avgustin, G (Folia microbiologica, 2004)
An in vitro study in dual-flow continuous-culture fermentors was conducted with two different concentrations of monensin, cinnamaldehyde or garlic extract added to 1:1 forage-to-concentrate diet in order to determine their effects on selected rumen bacterial populations. Samples were subjected to total DNA extraction, restriction analysis of PCR amplified parts of 16S rRNA genes (ARDRA) and subsequent analysis of the restriction profiles by lab-on-chip technology with the Agilent's Bioanalyser 2100. Eub338-BacPre primer pair was used to select for the bacteria from the genera Bacteroides, Porphyromonas and Prevotella, especially the latter representing the dominant Gram-negative bacterial population in the rumen. Preliminary results of HaeIII restriction analysis show that the effects of monensin, cinnamaldehyde and garlic extract on the BacPre targeted ruminal bacteria are somewhat different in regard to targeted populations and to the nature of the effect. Garlic extract was found to trigger the most intensive changes in the structure of the BacPre targeted population. Comparison of the in silico restriction analysis of BacPre sequences deposited in different DNA databanks and of the results of performed amplified ribosomal DNA restriction analysis showed differences between the predicted and obtained HaeIII restriction profiles, and suggested the presence of novel, still unknown Prevotella populations in studied samples.
Keywords: Bacteroides; Animals; Rumen; ribozomální DNA; Genes, rRNA; DNA, Ribosomal; Acrolein; Deoxyribonucleases, Type II Site-Specific; Monensin; DNA bakterií; DNA Fingerprinting; rostlinné extrakty; bakteriální geny; RNA, Ribosomal, 16S; monensin; DNA, Bacterial; Anti-Bacterial Agents; bachor; DNA fingerprinting; Prevotella; česnek; Bacteria; akrolein; Porphyromonas; restrikční endonukleasy typu II; Plant Extracts; ribotypizace; Genes, Bacterial; geny rRNA; Garlic; zvířata; antibakteriální látky; RNA ribozomální 16S; Ribotyping